Структурна ідентифікація різницевих операторів методами аналізу інтервальних даних - Войтюк, Ірина Федорівна (Національний університет "Львівська політехніка", 2012)
Дисертаційна робота присвячена актуальній науковій задачі структурної ідентифікації різницевих операторів на основі аналізу інтервальних даних, отриманих за результатами спостережень реальних процесів з похибками, обмеженими за амплітудою. Проаналізовано особливості застосування макромоделей у вигляді різницевих операторів для моделювання процесів в системах екологічного моніторингу. Проведено аналіз відомих методів та алгоритмів ідентифікації макромоделей об’єктів в умовах структурної невизначеності і сформульовано можливі напрями розвитку цих методів. Розроблені кількісні критерії оцінки якості та складності структури макромоделей у вигляді інтервальних різницевих операторів, перевірено їх працездатність для пошуку оптимальної структури моделі. Формалізовано задачу багатокритеріального синтезу структури макромоделей у вигляді різницевих операторів на основі інтервальних даних. Розроблено новий метод структурної ідентифікації макромоделей у вигляді різницевих операторів на основі аналізу інтервальних даних із застосуванням генетичних алгоритмів, зокрема проведено модифікацію відомих операцій селекції та схрещування. Розроблено програмне забезпечення та на його основі проведено апробацію розроблених методу та алгоритму структурної ідентифікації інтервального різницевого оператора для розв’язуванні задач макромоделювання процесів поширення концентрацій шкідливих викидів діоксиду азоту в м. Тернополі. Диссертационная работа посвящена решению актуальной научной задачи структурной идентификации разностных операторов на основе анализа интервальных данных, полученных по результатам наблюдений реальных процессов с погрешностями, ограниченными по амплитуде. Проанализированы особенности применения макромоделей в виде разностных операторов для моделирования процессов в системах экологического мониторинга. Проведен анализ известных методов и алгоритмов идентификации макромоделей объектов в условиях структурной неопределенности и сформулированы возможные направления развития этих методов. Разработаны количественные критерии оценки качества и сложности структуры макромоделей в виде интервального разностного оператора, проверено их работоспособность для поиска оптимальной структуры модели. Формализована задача многокритериального синтеза структуры макромоделей в виде разностных операторов на основе интервальных данных. Разработан новый метод структурной идентификации макромоделей в виде разностных операторов на основе анализа интервальных данных с применением генетических алгоритмов, в частности проведено модификацию известных операций селекции и скрещивания. Разработано программное обеспечение и на его основе проведена апробация разработанных метода и алгоритма структурной идентификации интервальных разностных операторов для решении задач макромоделирования процессов распространения концентраций выбросов диоксида азота в г. Тернополе. Dissertation is devoted to the actual scientific task of structure identification of difference operators based on analysis the interval data obtained in the observations of real processes with errors, bounded by the amplitude. It is analyzed the features of using the macromodels in kind of difference operators for modeling the processes in the environmental monitoring systems. It is conducted the analyzing the known methods and algorithms for identification the macromodels of objects in terms of structure uncertainty and the possible directions for development of these methods is formulated. It is shown that existing methods of macromodeling processes in the kind of difference operators in conditions of structure uncertainty are unsuitable for the synthesis of macromodels based on interval data analysis, as based on combinatorial algorithms and oriented to the verification of the model structure as the criterion of regularity. It is proved using the genetic algorithms for searching optimal model and to avoid combinatorial complexity of algorithms for realization the method of structure identification. Introduced and substantiated the concept of interval difference operator, which enables us to construct adequate models based on experimental data presented in interval form. The basis of the construction of such difference operator is the criterion for inclusion of discrete interval estimations of predicted output characteristics of the object on the basis of the received model in corridor of discrete interval values of this characteristic, derivable as a result of experiment. Proposed and substantiated indicators of estimation of quality of the model structure in the form of of interval difference operator, that, unlike existing, offered: a guaranteed accuracy of the macromodel within the errors of experimental data; quantitatively estimate the model complexity and completeness that is necessary for achieving the goal of modeling. It is verified the capacity of quantitative criteria for evaluating the quality and complexity of structure macromodels in the form of interval difference operators to find the optimal model structure. The task of multi-criteria synthesis of structure of macromodels in the form of difference operators on the basis of interval data is formalized. The new method of structure identification the macromodels in the kind of differentce operators on the basis of interval data using genetic algorithms is created. This method is marked the criterion of selection and decline of calculable complication. The features of the method are: estimation of the compatibility of interval systems of nonlinear algebraic equations at each iteration of searching optimal models to ensure the given accuracy; using the genetic algorithm with modified basic operation of the crossing, built on a «playing lottery» and with coding of chromosomes using the decimal system calculus. Thus input variables for realization of method are: the set of structure elements; interval, which includes the number of structure elements of optimal model; parameter, which is named the size of freedom of choice of the best models. So it provides a solution of multicriterion problem of structure identification the macromodel with guaranteed predicted properties and controlled complexity. The software is created and it is held the approbation of created method and algorithm of structure identification the interval difference operators for solving the tasks of macromodeling processes emissions of nitrogen dioxide concentrations in the city of Ternopil. It is established that the dynamics pollutant emissions of concentrations is largely depend from the the daily cycle of change of intensity of transport traffic. Based on real data with interval errors using the methods of structure identification the interval difference operator it is constructed the field emissions of nitrogen dioxide concentrations of vehicles in the center of Ternopil.
Структурная идентификация разностных операторов методами анализа интервальных данных
Structure identification the difference operators by the methods of interval data analysis
Keywords: різницевий оператор; структурна ідентифікація; інтервальні дані; генетичний алгоритм; разностный оператор; структурная идентификация; интервальные данные; критерии оптимальности; генетический алгоритм; критерії оптимальності; difference operator; structure identification; interval data; criteria of optimum; genetic algorithm